Islamic donations-based crowdfunding platforms in Malaysia: an evaluation of regulatory and shariah issues - Mat Radzi, Rafisah; Muhamed, Nurul Aini; Kamaruddin, Muhammad Iqmal Hisham; Wan Mohamad Nazarie, Wan Nur Faznie; Kamarubahrin, Aimi Fadzirul (Universitas Islam Negeri Ar-Raniry, 2024)
The emergence of innovative digital financial technologies has made donation-crowdfunding viable as a method that can supplement traditional fundraising mechanisms. Crowdfunding has recently gained worldwide attention as an alternative financing mechanism to the traditional fundraising methods for business ventures or social projects. While donation-crowdfunding which utilise platforms has demonstrated promising growth, there is no established legal framework available to accommodate its operation, especially for Islamic ones. Therefore, this study provides intuitive information pertaining to legal and Shariah issues in governing Islamic donation-based crowdfunding in Malaysia. Drawing from the conceptual framework of Islamic economics and qualitative data collection through semi-structured with six representatives of the Islamic donation-crowdfunding platforms, this study concludes that the issues associated with Malaysian regulations regimes and Shariah issues revolve around the donation-based crowdfunding platforms business model should be considered when devising a Shariah framework for donation-crowdfunding schemes. The findings will help policymakers to formulate and put in place the appropriate regulatory framework to facilitate Islamic donation-based crowdfunding practice.